2017
DOI: 10.1002/aic.15624
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the droplet drying characteristics of crystallization‐prone mannitol – experiments and modeling

Abstract: Spray‐dried mannitol is a potential lactose replacement in pharmaceutical formulations, yet the drying behavior of individual mannitol droplets within the spray chamber has not been fully understood. This work explored the drying characteristics of mannitol by employing the reaction engineering approach (REA) in data analysis. A glass filament single droplet drying technique was used to monitor the changes in droplet temperature, mass, and diameter. The drying kinetics data obtained clearly demonstrated the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…2014; Har et al. 2017), emulsion droplets (Mura et al. 2010) and nanoparticle-laden droplets (Pathak & Basu 2016 b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2014; Har et al. 2017), emulsion droplets (Mura et al. 2010) and nanoparticle-laden droplets (Pathak & Basu 2016 b ).…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous polymeric solutions are one of the classes of multi-component solutions utilized in spray drying applications (Fu, Woo & Chen 2012;Har et al 2017). Polymeric droplets have a multitude of applications ranging from targeted drug delivery, thin films and coatings to surface patterning (Wilms 2005;Pathak & Basu 2016a;Zhu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al later reviewed the most important aspects of the modeling technique and compared it to the CDRC approach [ 109 ]. Har et al applied REA to glass filament single droplet drying of mannitol and found that the REA was sensitive to its temperature dependent crystallization behavior allowing for direct interpretation of drying profiles [ 140 ]. Putranto et al utilized REA to model the intermittent drying of mango tissues and kaolin for varying temperature and humidity by firstly deriving the relative activation energy from continuous convective drying [ 141 , 142 ].…”
Section: Physics Of Particle Formation From a Drying Dropletmentioning
confidence: 99%
“…Therefore, simple yet effective methods of investigating single droplet drying kinetics, such as single droplet drying methods, are often applied. Amongst these techniques are optical levitation 10, electromagnetic levitation 11, 12, or suspending droplets via a thin wire or glass filament 13–17. Suspending a single droplet or particle in an ultrasonic levitator was implemented as a successful and well‐established experimental method to investigate the transport phenomena occurring on the surface of the droplet.…”
Section: Introductionmentioning
confidence: 99%